2022
DOI: 10.3390/antibiotics11010105
|View full text |Cite
|
Sign up to set email alerts
|

Management of Children Admitted to Hospitals across Bangladesh with Suspected or Confirmed COVID-19 and the Implications for the Future: A Nationwide Cross-Sectional Study

Abstract: There is an increasing focus on researching children admitted to hospital with new variants of COVID-19, combined with concerns with hyperinflammatory syndromes and the overuse of antimicrobials. Paediatric guidelines have been produced in Bangladesh to improve their care. Consequently, the objective is to document the management of children with COVID-19 among 24 hospitals in Bangladesh. Key outcome measures included the percentage prescribed different antimicrobials, adherence to paediatric guidelines and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
40
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 29 publications
(70 citation statements)
references
References 96 publications
17
40
2
Order By: Relevance
“…Nevertheless, studies from Asia are reporting high use of antibiotics including the study of Hassan et al , which reported extremely high use of antibiotics (92%) in COVID-19 patients [72] , however, this study was not included in our meta-analysis as it has not met our inclusion criteria. We are also aware of more recent studies in Asia reporting high rates since our analysis [22, 73] .…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Nevertheless, studies from Asia are reporting high use of antibiotics including the study of Hassan et al , which reported extremely high use of antibiotics (92%) in COVID-19 patients [72] , however, this study was not included in our meta-analysis as it has not met our inclusion criteria. We are also aware of more recent studies in Asia reporting high rates since our analysis [22, 73] .…”
Section: Discussionmentioning
confidence: 91%
“…Nevertheless, other respiratory viruses such as Middle East respiratory syndrome coronavirus (MERS-CoV) and SARS-CoV-1 have reported a very low prevalence of bacterial co-infection amongst infected patients [15,16] potentially attributable to the comparatively small number of cases reported [17] . Concerns regarding bacterial co-infection in COVID-19 patients has led to widespread use of antibiotics empirically in both hospital and community settings [18][19][20][21][22] . The significant increase in antibiotic prescribing during the pandemic challenges antimicrobial stewardship programmes and risks emergence of multi-drug resistant bacteria [23][24][25] , with their associated impact on morbidity, mortality and costs [26][27][28][29] .…”
Section: -Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibiotic resistance is a global public health threat and, if not dealt with now, will become a severe issue, rendering surgical procedures risky and life-threatening. The root causes of antibiotic resistance development are poor drug quality, wrong antibiotic suggestions, wrong doses, excessive human and animal usage, environmental pollution from hospital untreated hospital sewage samples [22,[51][52][53]. Along with these causes, we hypothesize that inaccurate identification of pathogens by diagnostic centers can also lead to antibiotic resistance.…”
Section: Misdiagnosis Can Be a Prospective Route Of Antibiotic Resist...mentioning
confidence: 99%
“…The SARS-CoV-2 virus is a rare cause of fetal inflammatory response syndrome (FIRS) [ 18 ] and can be associated with multisystem inflammatory syndrome in children (MIS-C) [ 19 ]. However, in Bangladesh, Kawasaki disease (KD)-like symptoms/hyperinflammatory syndromes are a real possibility among children admitted with COVID-19 across countries [ 20 ]. This is a concern, primarily as such children, including neonates, may be managed in pediatric intensive care units (ICUs), with mortality in such units higher in lower- and middle-income countries than higher-income countries [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%